2018
DOI: 10.5740/jaoacint.17-0288
|View full text |Cite
|
Sign up to set email alerts
|

Single-Laboratory Validation for Determination of Total Soluble Proanthocyanidins in Cranberry Using 4-Dimethylaminocinnamaldehyde

Abstract: American cranberry (Vaccinium macrocarpon) is native to Eastern North America. Recent studies have suggested that the A-type proanthocyanidins (PACs) in cranberries are effective in preventing urinary tract infection. To meet the growing interest in the cranberry market, an accurate, reliable, and simple method to determine PAC concentration is needed. In this study, a modified method using 4-dimethylaminocinnamaldehyde to quantify total PACs in cranberry products was validated. Cranberry juice extract powder,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…DMAC assay was performed to quantify total PACs in cranberry products according to a previous paper published by our group 21 . PAC standard A2 or cPAC was used as a standard, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…DMAC assay was performed to quantify total PACs in cranberry products according to a previous paper published by our group 21 . PAC standard A2 or cPAC was used as a standard, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Studies published by Sintara and Wallace indicated that the reaction achieved a steady state in 10 min, approx. (Sintara et al 2018;Wallace and Giusti, 2010). However, studies carried out here under the other experimental conditions showed slower processes (Fig.…”
Section: Kinetic Studies Of Flavanol-dmac Reactionsmentioning
confidence: 54%
“…Hence, DMAC is currently used for the global determination of PACs in food products, dietary supplements, and pharmaceuticals, thanks to some advantages, such as simplicity, short analysis time, use of relatively low-cost reagents and inexpensive equipment (Muceniece et al 2019). Some recent studies have been proposed to try to improve the performance of DMAC assays for the determination of flavanols and PACs (Sintara et al 2018). For instance, Payne et al have developed a 96-well plate version for increasing the sample throughput and studied selectivity issues regarding other phenolic compounds .…”
Section: Introductionmentioning
confidence: 99%
“…pH Stability. Because pH was a key factor affecting the deprotonation and solubility of proanthocyanidins, 24 the physical properties of microcapsules might change with pH values. Thus, we initially study the impact of pH on the physical stability of microcapsules suspended in distilled water and proanthocyanidin solutions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…23 Besides, the deprotonation of proanthocyanidins is affected by the acidic condition in the stomach, which will reduce the electrostatic repulsion and stability of microcapsules. 24 Consequently, it is necessary to elucidate how oil-based microcapsules encapsulated by proanthocyanidins behave in the gastrointestinal tract. An improved understanding of the gastrointestinal behavior of the microcapsules coated with proanthocyanidins would contribute to the design of beverages and foods with specific functions, such as targeted and controlled release, bioavailability improvement, or preservation enhancement.…”
Section: ■ Introductionmentioning
confidence: 99%